Education as a co-developed commodity in Finland? A rhetorical discourse analysis on business accelerator for EdTech startups - Nivanaho Nina; Lempinen Sonia; Seppänen Piia (Routledge, Taylor & Francis Group, 2025)
Education business and the actors involved in it have gained increasing global attention. However, little is known about the commercial actors participating in mainly publicly maintained comprehensive schooling in Finland and how the roles of teachers and schools are seen in this edu-business. In this article, we analyze ‘edu-business acceleration’ by a Finnish company, xEdu, that develops EdTech startups for the global education market. Using rhetorical discourse analysis, this case study identifies and analyzes xEdu’s aims for EdTech business in Finland, focusing particularly on the role assigned to teachers and schools in the business. Through these discourses, xEdu wishes to ‘scale up’ Finnish comprehensive schooling by utilizing both the reputation of Finnish education and the expertise of Finnish teachers. Building on a framework of the global education industry, we discuss the dominant EdTech discourses surrounding Finnish comprehensive schooling and how they are legitimized and promoted by versatile rhetorical means.